DILATED CARDIOMYOPATHY AND PREGNANCY – A DANGEROUS COMBINATION - Маисеенко, Дмитрий Александрович; Царюк, Анна Андреевна; Менцик, Марина Мубаракзяновна; Семенова, Юлия Евгеньевна (Mother and Baby in Kuzbass, 2025)
The article describes a clinical case of maternal mortality, with combination of dilated cardiomyopathy during pregnancy. The main thing is to seek medical help at the first unpleasant symptoms from the heart and not only during pregnancy. Early diagnosis of cardiovascular disease is important to prevent adverse outcomes for these patients. Doctors must be highly qualified to distinguish between normal and pathological conditions of pregnancy, but only if patients seek medical attention in a timely manner.